DOES BEETROOT JUICE LOWER BLOOD PRESSURE?: A SYSTEMATIC REVIEW - Erisna, Maya; Arma, Merisa Restiani; Sumarni, Sri; Triana, Hilma (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: Hypertension or high blood pressure has been a common global health problem for several years. The content of nitrate within beetroot helps to increase production of nitric oxide (NO) which serves as a vasodilator and has potency to reduce blood pressure. This study aims to determine the potential effect of beetroot juice on reducing blood pressure.Methods: This study was a systematic review based on the PRISMA protocol as a writing guideline. Data were obtained from PubMed, Science Direct, and Google Scholar databases. Keywords used consisted of ?beetroot?, ?beetroot juice?, ?blood pressure?, and ?hypertension.? The eligibility criteria were research written in English, years of publication from 2014 and above, and Randomized controlled trials of beetroot juice interventions on reducing blood pressure.Results: The literature search resulted in 376 records, and only 9 studies were in the systematic review. Six out of 9 studies showed significant results of blood pressure reduction, but the other three studies confirmed otherwise. A significant reduction of blood pressure was mostly observed in healthy subjects. The efficacy of beetroot juice supplementation is influenced by several factors, including gender, age, nutritional status (BMI), initial blood pressure, duration of supplementation, dose, and concentration of nitrate.Conclusions: Beetroot juice supplementation is not so useful on reducing blood pressure because it only has an acute effect in lowering blood pressure and its effects were also influenced by several factors.